2013
DOI: 10.3109/08820538.2013.810277
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Techniques to Improve the Ability of Optical Coherence Tomography to Detect Optic Neuritis

Abstract: ANN technique improves the capability of Spectralis OCT to detect MS disease and to distinguish MS eyes with or without antecedent ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…This result (acc: 95.8%; AUC: 0.958) was better than that obtained in previous works by Garcia-Martin et al . who also used Spectralis OCT: an AUC of 0.945 18 and an accuracy of 88.5% 16 using ANN. Compared to studies that used SS-OCT Triton to measure RNFL, Pérez del Palomar et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result (acc: 95.8%; AUC: 0.958) was better than that obtained in previous works by Garcia-Martin et al . who also used Spectralis OCT: an AUC of 0.945 18 and an accuracy of 88.5% 16 using ANN. Compared to studies that used SS-OCT Triton to measure RNFL, Pérez del Palomar et al .…”
Section: Discussionmentioning
confidence: 99%
“…2,12,55 In this way, some authors demonstrated its potential, in combination with artificial intelligence (AI), as an early diagnostic tool. Garcia-Martin et al 16 applied artificial neural network (ANN) to pRNFL thickness in order to analyse the ability of Spectralis OCT to diagnose MS. Cavaliere et al 9 designed a computer-aided diagnosis method using support vector machine (SVM) with mRNFL and pRNFL measurements performed by Triton SS-OCT from 48 MS patients and 48 healthy controls. These database was also used by Garcia-Martin et al 17 with a feed-forward neural network as a deep learning technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we explore the use of machine learning techniques to detect the disease using data from SS-OCT. To the best of our knowledge, this is the first study evaluating MS eyes using swept source OCT technology in combination with machine learning techniques. Some preliminary studies [13][14] have analyzed the role of these techniques using specific protocols and other OCT devices. Here, different protocols obtained by DRI OCT Triton were analyzed and compared in order to specify the success ratio of different machine learning techniques for determining MS disease.…”
Section: Introductionmentioning
confidence: 99%
“…In ihrer Studie aus dem Jahr 2015 erkannte der Algorithmus eine MS mit einer Sensitivität von 89,3 % und einer Spezifität von 87,6 %. Des Weiteren waren sie in der Lage bei MS-Patienten zwischen solchen mit Zustand nach Neuritis nervi optici und solche ohne zu entscheiden [36]. In ihrer Studie aus dem Jahr 2020 wurde für die Unterscheidung zwischen gesund und MS eine Sensitivität und eine Spezifität von 98 % erreicht [37].…”
Section: Neuroophthalmologieunclassified